Revisiting the public awareness of aphasia in Exeter: 16 years on. (3rd September 2019) - Hill, Asti; Blevins, Rachael; Code, Chris
Abstract: Background : Surveys of awareness of aphasia have been conducted worldwide. There has been no survey of change in awareness in one place over time. A survey in Exeter, UK in 2001 found awareness of aphasia was strikingly low. The aim of this study was to conduct a repeat survey using the same methods in the same city 16 years later to examine changes in awareness and knowledge. Method : We surveyed 167 shoppers in Exeter examining awareness and knowledge of aphasia. Awareness of stroke, stuttering, dyslexia and autism were examined for comparison. Demographic information was collected. Result : Thirty-four percent had heard of aphasia and 5% had some basic knowledge. Awareness of aphasia had improved significantly from 2001 to 2017, but basic knowledge had not. Awareness was higher in professional groups, such as lawyers and academics, and healthcare workers and in those who knew someone with aphasia. Awareness, but not knowledge, was higher in older respondents. Awareness of aphasia was significantly lower than awareness of all other conditions. Conclusion : We found a significant increase in awareness of aphasia in Exeter since 2001, but not knowledge. The implications of ongoing low levels of aphasia awareness, like inadequate funding and difficulty integrating into an ill-informed society, are discussed.